Differential elevational cline in the phenology and demography of two temporally isolated populations of a damselfly: Not two but one taxon?. (8th October 2018) - Amari, Hichem; Zebsa, Rabah; Lazli, Amel; Bensouilah, Soufyane; Mellal, Mohamed Khalil; Mahdjoub, Hayat; Houhamdi, Moussa; Khelifa, Rassim
Abstract : 1. Temporal isolation by cohort splitting is a life‐history mechanism that has been reported in many temperate insects, including those inhabiting freshwater habitats. Although the cohorts seem to maintain separate temporal niches in a specific location, the temporal isolation may be disrupted across a geographic gradient due to constraints imposed by seasonality. 2. This prediction was tested on two temporally isolated populations of the obligatory univoltine Lestes virens (Odonata, Lestidae) in north‐east Algeria. Although the two cohorts emerge at the same time in spring, one cohort reproduces in summer, while the second cohort estivates in summer and reproduces in autumn. A survey assessing the phenology and abundance was conducted on eight ponds across an elevational gradient (5–1012 m asl) using capture–mark–recapture and adult density sampling. 3. In all sites from low to high elevation, the species showed cohort splitting. The phenology of reproduction of both cohorts showed a delay with elevation, but the cline was 2.2 days for the summer cohort and 0.7 days for the autumn cohort per 100 m of elevation. Moreover, the density of adults in the autumn cohort was higher than that of summer cohort across the entire elevational range, and the difference increased with elevation. 4. These findings regarding the differential elevational cline in the phenology show that the temporal isolation of the two cohorts becomes narrower at high elevation, suggesting potential inter‐cohort temporal overlap at higher elevations. 5. The claim that the two cohorts of L. virens are true temporally isolated species needs further investigation. Abstract : Lestes virens is a damselfly that shows sympatric cohort split behaviour in North Africa, but it is still unknown whether the cohorts maintain temporal isolation across the elevational gradient. The phenology of the two cohorts (summer and autumn) shifted to later dates with elevation, but the temporal distance between them declines with potential overlap at around 1000 m. The abundance of the autumn cohort was higher than that of the summer cohort across the entire elevation gradient, and more so at higher elevations.